HUBUNGAN ANTARA BUDAYA ORGANISASI DAN SAFETY AWARENESS TERHADAP KEPATUHAN KESELAMATAN DAN KESEHATAN KERJA (K3) DI PT X MAKASSAR - Firmansyah, Fachrizal; Affandi, Ghozali Rusyid (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research is motivated by problems related to compliance with Occupational Safety and Health (K3) at PT X Makassar. Many employees lack awareness of occupational safety and health, excessive stress levels and workloads, and an imbalance in productivity and safety culture. The purpose of this study is to determine the relationship between organizational culture and safety awareness and compliance with occupational safety and health (K3). This research method is quantitative with a sampling technique using saturated samples, the subjects are 250 company employees. The variables in this study are organizational culture, safety awareness and compliance with occupational safety and health. Data collection in this study used a Likert scale model psychology compilation scale created by the researcher. The hypothesis in this study is that there is a positive relationship between organizational culture and safety awareness and compliance with occupational safety and health. Data analysis in this study used the Pearson product moment correlation statistical test with the help of SPSS 26.0 for Windows. The results of the study obtained that the value of rx1y = 0.125, p = 0.045 <0.05 and the value of rx2y = 0.532, p = 0.000 <0.05. The higher the organizational culture and self-awareness owned by employees, the higher the compliance with K3 and vice versa.